Does Argininosuccinate Synthase 1 (ASS1) Immunohistochemistry Predict an Increased Risk of Hemorrhage for Hepatocellular Adenomas?. Issue 6 (July 2020) - Lehrke, Heidi D.; Van Treeck, Benjamin J.; Allende, Daniela; Denham, Laura J.; Gonzalez, Raul S.; Moreira, Roger K.; Mounajjed, Taofic; Naini, Bita V.; Smoot, Rory L.; Zreik, Riyam T.; Jenkins, Sarah; Graham, Rondell P.
Abstract : Hepatocellular adenomas (HCAs) often pursue an innocuous clinical course. Recent work has elucidated important subtypes of HCA and biomarkers to identify them, including HCA at an increased risk for malignant transformation. Another key complication of HCAs is the risk of spontaneous tumoral hemorrhage, which may be life-threatening. Identification of a predictive biomarker for this clinical complication would therefore be of clinical value. It has been suggested that Argininosuccinate Synthase 1 (ASS1) immunohistochemistry (IHC) identifies HCA with a high propensity for hemorrhage. The aim of our study was to validate ASS1 IHC as a predictive marker of hemorrhage. Eighty-nine HCAs were collected for ASS1 IHC and subtyped according to published criteria. Clinical records were examined for evidence of tumoral hemorrhage. Twenty-one (23.6%) HCAs were complicated by clinically detected hemorrhage and were more likely to be resected ( P =0.0002). Hemorrhage complicated all WHO subtypes of HCA. There was no association between hemorrhage and HCA subtype ( P =0.92). Neither the distribution of ASS1 expression nor the intensity of ASS1 expression compared to normal liver showed a significant association with hemorrhage ( P =0.051 and 0.34). Interlaboratory comparison of 8 cases showed good agreement regarding the intensity (6/8 and 7/8) and distribution of staining (7/8 and 7/8) across 3 laboratories performing ASS1 IHC. In conclusion, all subtypes of HCA may be complicated by hemorrhage. ASS1 IHC expression did not correlate with hemorrhagic complications. Caution is prudent before routine implementation of ASS1 IHC in clinical practice. Abstract : Supplemental Digital Content is available in the text.